Determinants of Transfer Pricing Aggressiveness of Consumer Goods Companies in Indonesia with Financial Performance as a Mediating Variable - Supriyadi SUPRIYADI; Tri WIDYASTUTI; Darmansyah DARMANSYAH (International Journal of Environmental, Sustainability, and Social Science, 2025)
Transfer Pricing Aggressiveness (TPA) is a strategy by multinational companies to shift profits to low-tax jurisdictions, which poses serious challenges for tax authorities in the context of Base Erosion and Profit Shifting (BEPS). Consumer goods companies in Indonesia are vulnerable to this practice due to characteristics such as leverage, company size, intangible assets, and the effective tax rate. This study aims to analyze the main determinants of TPA and explore the mediating role of financial performance in this relationship. The approach used is a mixed methods approach with an explanatory sequential design. Quantitative data were obtained from 126 financial reports of Indonesian consumer goods companies for the period 2016–2022 and analyzed using SEM-PLS. The results show that financial characteristics significantly influence TPA through financial performance as a mediator. Large and highly leveraged companies tend to manage TPA strategically, while the use of intangible assets is carried out more cautiously due to valuation and oversight risks. Financial performance serves as a signal to stakeholders and a legitimacy tool in the face of regulatory pressure. This research integrates various theoretical perspectives: Agency Theory, Resource-Based View, Institutional Theory, Tax Compliance Theory, and Legitimacy Theory. Qualitative analysis reveals regulatory challenges in Indonesia, particularly in oversight, compliance, and dispute resolution. This research provides empirical and conceptual contributions to understanding TPA strategies in developing countries and supports governance- and data-driven fiscal reforms.